2015
DOI: 10.1017/s0016672315000166
|View full text |Cite
|
Sign up to set email alerts
|

The long tail and rare disease research: the impact of next-generation sequencing for rare Mendelian disorders

Abstract: There are an estimated 6000-8000 rare Mendelian diseases that collectively affect 30 million individuals in the United States. The low incidence and prevalence of these diseases present significant challenges to improving diagnostics and treatments. Next-generation sequencing (NGS) technologies have revolutionized research of rare diseases. This article will first comment on the effectiveness of NGS through the lens of long-tailed economics. We then provide an overview of recent developments and challenges of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 89 publications
0
19
0
Order By: Relevance
“…We used a human phenotype ontology (HPO) term (Shen et al, ) to classify the primary disease of the patient that can be annotated by his clinical notes, which is essential for variant interpretation in our cohort characteristic of clinically and genetically heterogeneous disorders.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used a human phenotype ontology (HPO) term (Shen et al, ) to classify the primary disease of the patient that can be annotated by his clinical notes, which is essential for variant interpretation in our cohort characteristic of clinically and genetically heterogeneous disorders.…”
Section: Methodsmentioning
confidence: 99%
“…Although traditional gene mapping approaches, such as Sanger sequencing (Botstein & Risch, ), linkage analysis (Teare & Santibanez Koref, ), and homozygosity mapping (Lander & Botstein, ) have led to great insights into Mendelian diseases over the past few decades; they are unable to detect all forms of variation in a single experiment. The rapid development of next generation sequencing (NGS) constituted a turning point for the advancement of our understanding of this type of diseases, which requires a broad search for causal variants across their genetically heterogeneous spectrum within a short time (Shen, Lee, Shen, & Lin, ), especially for life‐threatening or chronically debilitating cases. Today, different NGS techniques can be used for diagnostic purposes.…”
Section: Introductionmentioning
confidence: 99%
“…For ‘ultrarare’ diseases, in which candidate variants have only been identified in a handful of individuals within a single pedigree, validation of pathogenicity can be challenging. Additionally, because translational research efforts have historically been more focused on common disorders,7 the underlying mechanisms contributing to rare diseases often remain poorly understood, even where the genetic aetiology has been confirmed.…”
Section: The Importance Of Researching Rare Genetic Diseasesmentioning
confidence: 99%
“…In the last decade, next-generation sequencing (NGS) has emerged as an effective tool for detecting single nucleotide variants (SNVs) causing rare conditions [1]. Recent retrospective studies have demonstrated an increase of 25-31% in diagnostic yield of rare diseases due to the application of exome or whole genome sequencing in a clinical framework [2,3]. Through comparison against human genome reference sequence, high-quality NGS data on individual patients can be used to identify variation in variant call files (VCF).…”
Section: Introductionmentioning
confidence: 99%